Environmental changes in the north‐east Sunda region over the last 40 000 years. (21st March 2019) - Luo, Chuanxiu; Haberle, Simon; Zheng, Zhuo; Xiang, Rong; Chen, Chixin; Lin, Gang; Sazal, Kumar
ABSTRACT: Pollen and spores from 110 samples from sediment core NS07‐25 from the Nansha Trough in the South China Sea (SCS) were analysed with a particular focus on reconstructing vegetation and climate change and identifying the sources of palynomorphs on the Sunda Shelf during the Last Glacial Maximum (LGM). Palynomorph sources were identified using the Near Analysis function in ArcGIS with 62 data points of the pollen in surface sediment samples from the southern SCS. The results showed that during the LGM, pollen and spores came from the exposed Sundaland, whereas before and after the LGM, pollen and spores came from Borneo. Changes in vegetation and climate were inferred from pollen percentages, concentrations and influx and indicated that during the LGM, ferns, lowland rainforests, upper montane rainforests and lower montane forests were present on the north‐east part of the exposed Sunda Shelf but not over the entire Sunda Shelf. Climate during the LGM was cooler than it is today, but humidity was not substantially lower. During the LGM, grasses and shrubs did not cover the southern continental shelf of the SCS, possibly because they were located in the Intertropical Convergence Zone.